2020
DOI: 10.1111/trf.15763
|View full text |Cite
|
Sign up to set email alerts
|

Is sporadic Creutzfeldt‐Jakob disease transfusion‐transmissible?

Abstract: http://onlinelibrary.wiley.com/doi/10.1111/trf.15751/full

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…3,4 Thus, the consensus from these studies is that the risk, if any, of transfusion transmission of classic CJD is extremely low. [5][6][7] Of note, a report from the UK in 2017 shows sporadic CJD in two recipients of plasma products with long-term treatment, however a causal link to these products was not established. 8 The conclusion that CJD is unlikely to be transmitted by transfusion accompanies recognition that there is no longer significant risk of transmission of vCJD; the last reported transfusion transmission of vCJD worldwide was in 2007.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 Thus, the consensus from these studies is that the risk, if any, of transfusion transmission of classic CJD is extremely low. [5][6][7] Of note, a report from the UK in 2017 shows sporadic CJD in two recipients of plasma products with long-term treatment, however a causal link to these products was not established. 8 The conclusion that CJD is unlikely to be transmitted by transfusion accompanies recognition that there is no longer significant risk of transmission of vCJD; the last reported transfusion transmission of vCJD worldwide was in 2007.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, comparable studies from the UK and Scandinavia found no cases among respectively 1194 and 7617 person years of observation, for an overall total of more than 15,500 person‐years 3,4 . Thus, the consensus from these studies is that the risk, if any, of transfusion transmission of classic CJD is extremely low 5–7 . Of note, a report from the UK in 2017 shows sporadic CJD in two recipients of plasma products with long‐term treatment, however a causal link to these products was not established 8 …”
Section: Discussionmentioning
confidence: 99%
“…PrP TSE is present in plasma EVs of symptomatic and asymptomatic mice infected with prions (59, 60). Thus, via blood transfusion, EVs can contribute to recorded horizontal infection with variant CJD (61). The involvement of EVs in the oral pathway of infection is also possible since EVs can survive the stomach environment (62, 63).…”
Section: Introductionmentioning
confidence: 99%
“…PrP TSE is present in plasma EVs of symptomatic and asymptomatic mice infected with prions (59,60). Thus, via blood transfusion, EVs can contribute to recorded horizontal infection with variant CJD (61).…”
Section: Introductionmentioning
confidence: 99%